2019
DOI: 10.1111/cge.13602
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic mutations in Sperm flagellum 2 cause human multiple morphological abnormalities of the sperm flagella (MMAF) phenotype

Abstract: Male patients with multiple morphological abnormalities of the sperm flagella (MMAF) are infertile and exhibit absent, short, coiled, bent and/or irregular sperm flagella. Mutations in the SPEF2 gene reduce sperm motility and cause sperm tail defects in animal models and humans. In the present study, we performed a genetic analysis on an MMAF patient and identified novel biallelic mutations in the SPEF2 gene. The biallelic mutations were confirmed by Sanger sequencing and in silico analysis revealed that, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…MMAF is an autosomal‐recessive disorder linked to mutations in several genes, including DNAH1 (Ben Khelifa et al., ; Wang et al., ), DNAH2 (Li et al., ), CFAP43 , and CFAP44 (Sha et al., ; Tang et al., ; Wu et al., ), CFAP69 (Dong et al., ; He et al., ), CFAP251 (also known as WDR66 ) (Kherraf et al., ; Li et al., ), FSIP2 (Martinez et al., ), ARMC2 (Coutton et al., ), AK7 ( Lores et al., ), QRICH2 (Shen et al., ), SPEF2 (Liu et al., ; Sha et al., ), TTC21A (Liu et al., ), and CEP135 (Sha et al., ). However, further research is needed to determine the genetic causes of the remaining 40%–50% of the MMAF patients (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…MMAF is an autosomal‐recessive disorder linked to mutations in several genes, including DNAH1 (Ben Khelifa et al., ; Wang et al., ), DNAH2 (Li et al., ), CFAP43 , and CFAP44 (Sha et al., ; Tang et al., ; Wu et al., ), CFAP69 (Dong et al., ; He et al., ), CFAP251 (also known as WDR66 ) (Kherraf et al., ; Li et al., ), FSIP2 (Martinez et al., ), ARMC2 (Coutton et al., ), AK7 ( Lores et al., ), QRICH2 (Shen et al., ), SPEF2 (Liu et al., ; Sha et al., ), TTC21A (Liu et al., ), and CEP135 (Sha et al., ). However, further research is needed to determine the genetic causes of the remaining 40%–50% of the MMAF patients (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in CFAP69 were also found in infertile men who exhibited severe flagellar abnormalities, including flagella being short, coiled, absent, and of irregular caliber, which is referred to as multiple morphological abnormalities of the flagella (MMAF) [ 12 , 17 ]. Variations in another CP component, SPEF2, were found in MMAF patients as well [ 29 , 30 , 52 , 63 ], suggesting that CP components are important for sperm flagellar formation not only in mice but also humans.…”
Section: Ko Mouse Lines That Do Not Exhibit Premature Lethalitymentioning
confidence: 99%
“…There are two evolutionarily conserved bidirectional transport platforms that are involved in sperm flagellum biogenesis, including intramanchette transport (IMT) and intraflagellar transport (IFT) (Kierszenbaum, 2001(Kierszenbaum, , 2002San Agustin et al, 2015). IMT and IFT share similar cytoskeletal components, namely microtubules and F-actin, that provide tracks for the transport of structural proteins to the developing tail (Kierszenbaum et al, 2011a), and mutations in TTC21A, TTC29, SPEF2, and CFAP69, which have been reported to disrupt sperm flagellar protein transport, also lead to MMAF (Dong et al, 2018;Liu C. et al, 2019;Sha et al, 2019;Liu et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%